2017
DOI: 10.11114/jets.v5i9.2625
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Lean method in English Language Teaching and Learning: A New Perspective

Abstract: Lean is regarded as a systematic approach to maximizing value by minimizing waste, and by flowing the product or service at the pull of the customer demand. These key concepts of "value," "flow," and "pull," align with the ultimate lean goal: "perfection," or a continuous striving for improvement in the performance of the organization. Through applying a lean methodology to the teaching processes, additionally the teachers can eliminate reasons that do not add value and are thus wasteful, and they can focus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The results showed that younger teachers were more confident and willing to use gamification in their lessons, while older teachers may need more support and training to effectively incorporate it into their teaching. This finding is consistent with previous research that suggests younger teachers may be more comfortable with technology (David & Aruta, 2022;Joiner et al, 2013) and more open to experimentation with new teaching methods (Tilfarlioglu & Anwer, 2017).…”
Section: Age Range Vs Intention Of Using Gamification In Classsupporting
confidence: 92%
“…The results showed that younger teachers were more confident and willing to use gamification in their lessons, while older teachers may need more support and training to effectively incorporate it into their teaching. This finding is consistent with previous research that suggests younger teachers may be more comfortable with technology (David & Aruta, 2022;Joiner et al, 2013) and more open to experimentation with new teaching methods (Tilfarlioglu & Anwer, 2017).…”
Section: Age Range Vs Intention Of Using Gamification In Classsupporting
confidence: 92%
“…Setting some particular objective in transforming the administrative process (Solaimani et al, 2019), work instruction, student passes rate, teaching training, feedback, each unit performance check and assessment will greatly improve the quality of teaching and learning (Tılfarlıoğlu & Anwer, 2017). Thus the record keeping system and document searching problem will be reducing as well.…”
Section: Standardizationmentioning
confidence: 99%